Archery under the (electroencephalography-)hood: Theta-lateralization as a marker for motor learning - Rampp, Stefan; Spindler, Kai; Hartwigsen, Gesa; Scheller, Christian; Simmermacher, Sebastian; Scheer, Maximilian; Strauss, Christian; Prell, Julian (Neuroscience, 2022)
An intrinsic characteristic of the motor system is the preference of one side of the body. Lateralization is found in motor behavior and in the structural and functional correlates of cortical motor networks. While genetic factors have been elucidated as mechanisms leading to such asymmetries, findings in motor learning and experience from clinical experience demonstrate considerable additional plasticity during the lifespan. If and how functional lateralization develops in short timeframes during training of motor skills involving both sides of the body is still largely unclear. In the present exploratory study, we investigate lateralization of theta-, alpha- and beta-band oscillations during training of an ecologically valid skill – archery. We relate lateralization shift to performance improvement and elucidate the underlying cortical areas. To this end, healthy participants without any previous experience in archery underwent intensive training with 100 shots on each of three days. 64-channel electroencephalography was recorded simultaneously during the individual shots. We found that a central-parietal theta lateralization shift to the left immediately before the shot was associated with performance improvement. Lateralization of alpha or beta did not yield a significant association. Importantly, areas of maximum activation were not identical with areas showing the strongest associations with performance improvement. These data suggest that learning a complex bimanual motor skill is associated with a shift of theta-band oscillations to the left in central-parietal areas. The relationship with performance improvement may reflect increased cortical efficiency of task-relevant processing.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Beta; Electroencephalography; Lateralization; Learning; Motor; Theta